Coral Disease Time Series Highlight Size-Dependent Risk and Other Drivers of White Syndrome in a Multi-Species Model - Greene, Austin; Donahue, Megan J.; Caldwell, Jamie M.; Heron, Scott F.; Geiger, Erick; Raymundo, Laurie J. (Frontiers in Marine Science, 2020)
Coral diseases contribute to the decline of reef communities, but factors that lead to disease are difficult to detect. In the present study, we develop a multi-species model of colony-scale risk for the class of coral diseases referred to as White Syndromes, investigating the role of current or past conditions, including both environmental stressors and biological drivers at the colony and community scales. Investigating seven years of coral survey data at five sites in Guam we identify multiple environmental and ecological associations with White Syndrome, including a negative relationship between short-term heat stress and White Syndrome occurrence, and strong evidence of increasing size-dependent White Syndrome risk across coral species. Our findings result in a generalized model used to predict colony-scale White Syndrome risk for multiple species, highlighting the value of long-term monitoring efforts to detect drivers of coral disease.